Phloem Regeneration Is a Mechanism for Huanglongbing-Tolerance of “Bearss” Lemon and “LB8-9” Sugar Belle® Mandarin - Deng, Honghong; Achor, Diann; Exteberria, Ed; Yu, Qibin; Du, Dongliang; Stanton, Daniel; Liang, Guolu; Gmitter Jr., Fred G. (Frontiers in Plant Science, 2019)
Huanglongbing (HLB) is an extremely destructive and lethal disease of citrus worldwide, presumably caused by a phloem-limited bacteria, Candidatus Liberibacter asiaticus (CLas). The widespread invasiveness of the HLB pathogen and lack of natural HLB-resistant citrus cultivars have underscored the need for identifying tolerant citrus genotypes to support the current citrus industry’s survival and potentially to lead to future natural HLB resistance. In this study, transverse sections of leaf lamina and midribs were examined with light and epifluorescence microscopy to determine anatomical characteristics that underlie HLB-tolerant mechanisms operating among ‘Bearss’ lemon, ‘LB8-9’ Sugar Belle® mandarin, and its sibling trees compared with HLB-sensitive ‘Valencia’ sweet orange. The common anatomical aberrations observed in all CLas-infected varieties are as follows: phloem necrosis, hypertrophic phloem parenchyma cells, phloem plugging with abundant callose depositions, phloem collapse with cell wall distortion and thickening, excessive starch accumulation and sometimes even cambium degeneration. Anatomical distribution of starch accumulation even extended to tracheid elements. Although there were physical, morphological and pathological similarities in the examined foliage, internal structural preservation in ‘Bearss’ lemon and ‘LB8-9’ Sugar Belle® mandarin was superior compared with HLB-sensitive ‘Valencia’ sweet orange and siblings of ‘LB8-9’ Sugar Belle® mandarin. Intriguingly, there was substantial phloem regeneration in the tolerant types that may compensate for the dysfunctional phloem, in comparison with the sensitive selections. The lower levels of phloem disruption, together with greater phloem regeneration, are two key elements that contribute to HLB tolerance in diverse citrus cultivars.